Smart analytics, artificial intelligence and sustainable performance management in a global digitalised economy. Part A - Tyagi, Pallavi; Grima, Simon; Sood, Kiran; Balusamy, Balamurugan; Özen, Ercan; Thalassinos, Eleftherios (Contemporary studies in economic and financial analysis ;, 2023)
The Covid 19 pandemic has created chaos in the business world and forced leaders to rethink their operational status quo. Balancing the physical and virtual spaces of the global digital economy wherein economic, commercial, and professional transactions are enabled by information and communication technologies has called for additional support from data-driven technologies like smart analytics and artificial intelligence. Opportunities created within digital economies to leverage technologies to execute tasks better, faster, and often differently have found the desired prominence in the recent past. Though the benefits outweigh the risks, the challenges in digitalised economies are as sophisticated as the solutions they offer. Smart Analytics, Artificial Intelligence and Sustainable Performance Management in a Global Digitalized Economy presents various viewpoints on topics like artificial intelligence, blockchain technology, digitalisation in various sectors, technology issues like cybersecurity and financial inclusion, and technology-enabled banking issues like money laundering. The theme of sustainability forms the core of the book.